A produção de energia: usos políticos e econômicos do território e desenvolvimento rural no Vale do Zambeze, Moçambique - A barragem de Cahora Bassa em questão - Mungói, Cláudio Artur (GEOUSP Espaço e Tempo (Online), 2011)
The aim of this paper is to demonstrate that the countryside is not only the agricultural. Also the Infrastructures have been played an important role in the strategic development of the Zambezi Valley region. This means that rural development also depends on actions and strategic infrastructure provisions that go beyond the restricted field of the agricultural sector. Take as example the Cahora Bassa Dam analyzed as possible locomotive for the development of the region and strongly linked to political and economic uses of the territory, which places reason at the top of political and economic agenda and, therefore, need to understand the formulation of regional policies. Territorial policies are understood here as the set of actions aimed at the state investment in infrastructure and development programs can generate significant social and economic changes at local and regional level.